PENGARUH SISTEM PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI, DAN KOMPETENSI APARATUR DESA TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI EMPIRIS PADA DESA-DESA DI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR) - Fadila, Doremi; Armel, R.Septian; Suriyanti, Linda Hetri (LPPM Universitas Putera Batam, 2025)
This research aims to determine the influence of the internal control system, organizational commitment and competency of village officials on the accountability of village fund management in villages in Tapung Hilir District, Kampar Regency. The method used in research is a quantitative method. The population in this study were all village officials including the Village Head, Village Secretary, Head of Section/Government Affairs, Head of Section/Development Affairs, Head of Section/Community Empowerment Affairs, Head of Section/People's Welfare Affairs, Head of Section/General Affairs, and Head Sections/Financial Affairs in Tapung Hilir District, Kampar Regency, totaling 128. The sample used was purposive sampling, totaling 64 respondents. The data collection used was a questionnaire distributed to Village Apparatus officials in Tapung Hilir District, Kampar Regency. Data were analyzed using the SPSS 22 program. The results of the analysis show that the finding that the internal control system has a positive effect on village fund management accountability and the correlation between the internal control system variables and the Village Fund Management Accountability variable shows a correlation of 0.220, which means that the correlation coefficient is at a low level of relationship, namely 0.20-0.399. Competency of village officials has a positive effect on accountability in managing village funds and the correlation between the variable organizational commitment, internal control system of funds, the variable Village Fund Management Accountability shows a correlation of 0.227, which means that the magnitude of the correlation coefficient is at a low level of relationship, namely 0.20-0.399, while organizational commitment has no effect on accountability in village fund management and the correlation between the apparatus competency variable and the Village Fund Management Accountability variable shows 0.020, which means the correlation coefficient is at a very low level of relationship, namely 0.00-0.199.